The Effect Of Giving Cinnamon Aromatherapy On Primary Dysminore In Adolescent's Class 3 Junior High School In SMPN 1 Bekasi City - Lika Malikal M; Resi Galaupa (East Asian Journal of Multidisciplinary Research, 2022)
Dysmenorrhea is the most common gynecological complaint that women experience, especially when entering their teens. This study was aimed to determine the effect of cinnamon (Cinnamomum Burmanni) aromatherapy by inhalation on the intensity of primary dysmenorrhea in female students of SMPN 1 Bekasi. The method used in this study is a quasi-experimental or quasi-experimental design which is an experimental activity aimed at seeing an effect or symptom that appears due to a certain treatment, using a sample of 30 samples. Of the 30 respondents, the average score before the intervention was 6.067 while after the intervention the average score was 3.100.